Marital Satisfaction as a Risk Marker for Intimate Partner Physical Violence: A Meta-analytic Review - Stith, Sandra M.; Green, Narika M.; Smith, Douglas B.; Ward, David B. (My University, 2010)
A meta-analysis investigating the relationship between marital satisfaction and intimate partner violence (IPV) was conducted with 32 articles. Overall, a small-to-moderate effect size (r = -.27) indicated a significant and negative relationship existed between marital satisfaction and IPV. Moderator analyses found no differences between effect size based on construct examined (discord or satisfaction). However, the magnitudes of observed effect sizes were influenced by other moderator variables, including the use of standardized versus non-standardized measures, gender of the offender and victim, role in the violence (perpetrator versus victim), and sample type (clinical versus community). The data suggests that gender is an especially important moderator variable in understanding the relationship between marital satisfaction and IPV.
Keywords: Marital satisfaction; Marital discord; Risk markers; Intimate partner violence; Gender; Meta-analysis